Occurrence of Adrenal Suppression in Patients Having Sepsis in Indian Population and Impact of Corticosteroid Supplementation on Its Overall Survival - Kamalakanta Swain (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Objective Our aim was to estimate the occurrence of adrenal suppression in critically ill patients with septic shock who have got admission in intensive care unit and to evaluate the effectiveness of hydrocortisone in these patients in relation to mortality of patient, development of septic shock, and effect on total leucocyte count. Methods Serum cortisol was measured in 120 patients with sepsis. Patients with decreased cortisol level were split in to two groups (group A and B). Group A received 50 mg of hydrocortisone 6 hourly and group B was given matching placebo. At day 7, serum cortisol level was estimated for both A and B groups. The results were calculated and compared with relation to incidence of adrenal insufficiency, development of septic shock, effect on total leucocyte count, and survival at 28 days. Results The occurrence of adrenal suppression in patients having sepsis in our study was 44 out of 120 patients, that is, 36.6%. After supplementation of corticosteroid for 7 days the mean value of serum cortisol of group A was 40.38 ± 8.44 µg/dL and group B was 24.30 ± 6.47 µg/dL (p < 0.001). At day 7, in group A, 22.7% developed septic shock, whereas in group B, 36.4% developed septic shock (p < 0.001). In group A and B, mortality rate of the patients at 28 days was 18.2 and 22.7%, respectively. Conclusion Hydrocortisone supplementation in critically ill patients with low random basal serum cortisol level with sepsis does not significantly improve the overall survival.